2012
DOI: 10.21273/horttech.22.4.430
|View full text |Cite
|
Sign up to set email alerts
|

Gardening Increases Vegetable Consumption in School-aged Children: A Meta-analytical Synthesis

Abstract: Although a handful of published reports suggest that garden-based nutrition education programs are effective in increasing fruit and vegetable consumption, many of these studies have low statistical power because of small sample sizes and lack of long-term data. In this study, we used meta-analytical techniques to examine the efficacy of garden-based nutrition education programs for increasing children’s nutrition knowledge, preference for fruit and vegetables, and/or consumption of fruit and vegetable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 34 publications
1
76
1
12
Order By: Relevance
“…Third, gardens, especially allotment and community gardens, provide opportunities to interact with other members of local communities, which is likely to forge and reinforce social ties, community networks, and sense of community (van den Berg et al, 2010, Wakefield et al, 2007). Fourth, and most indirectly, engagement in gardening could ensure people have a healthier diet, rich in fruits and vegetables (Langellotto and Gupta, 2012). Given these widespread benefits coming from gardening, we should consider gardens as an important and promising health resource for the local community.…”
Section: Discussionmentioning
confidence: 99%
“…Third, gardens, especially allotment and community gardens, provide opportunities to interact with other members of local communities, which is likely to forge and reinforce social ties, community networks, and sense of community (van den Berg et al, 2010, Wakefield et al, 2007). Fourth, and most indirectly, engagement in gardening could ensure people have a healthier diet, rich in fruits and vegetables (Langellotto and Gupta, 2012). Given these widespread benefits coming from gardening, we should consider gardens as an important and promising health resource for the local community.…”
Section: Discussionmentioning
confidence: 99%
“…Moderator analyses might explain why some interventions are more effective than others and could increase the effectiveness of future interventions. In this respect, a broad framework for moderator analyses (28) that has been adopted often (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) and includes participant features (i.e. participant age, gender, ethnicity and overweight/obesity risk) and intervention features (e.g.…”
mentioning
confidence: 99%
“…The results were consistent in the two studies assessing this age group. Western studies have also reported improved dietary awareness among preschoolers who participate in gardens [9][10][11]. There may have been an increase in interest and preference due to increased exposure [43].…”
Section: Dietary Knowledge and Awarenessmentioning
confidence: 99%
“…On a global scale, multiple systematic reviews and quick scans have discussed the associations between food production experiences and dietary knowledge, awareness, behavior, and health [2][3][4][5][6][7][8][9][10][11][12][13]. Studies have considered urban gardens [2,3], community gardens [4][5][6], school gardens [7][8][9], under the International Prospective Register of Systematic Reviews (PROSPERO; registration number: CRD42019117163) [21].…”
Section: Introductionmentioning
confidence: 99%